Studies in the Effect of Intensity and Solvent on the Course of Photolysis of 5,5-diphenylhydantoin - Jain, Shubha; Pandey, Rajbala; Kheradia, Binita (Asian Journal of Chemistry, 2016)
5,5-Diphenylhydantoin (I) when irradiated by low and high intensity UV source in ethanol gave product (II) and in acetic acid gave urea (III) and benzophenone (IV), in different yields and in different time. The structure of product (II) has been established by spectral and elemental analysis whereas products (III) and (IV) have been identified by mixed melting point and co-TLC with authentic samples.